Professor Frank Debenham Founder and First Director of the Scott Polar Research Institute-An Appreciation - Mill, Hugh Robert (Polar Record, 1947)
The highest good that life can confer upon anyone is to see a piece of work, begun in a moment of inspiration, prepared on a wall-considered plan, and completed to perfection by one's own efforts, and on this rare and happy achievement we offer our heartiest congratulations to Professor Debenham. In No. 29 of The Polar Record he has told the whole story of the inception, rise and progress of the Scott Polar Research Institute of the University of Cambridge. It is a prose saga of high ideals and great deeds modestly stated in the graceful flow of words of which he is a master. Many of us had deplored the waste of effort in so many great polar expeditions, each undertaken afresh with scant help from the scattered original records of earlier work, each ending with its members dispersed and the accumulated data scattered once more; but it was Frank Debenham alone who formulated the remedy.